2008
DOI: 10.1016/j.fertnstert.2007.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: increased gonadotropin use for ovarian stimulation adversely influences clinical pregnancy and live birth after in vitro fertilization

Abstract: Our data add to the accruing literature suggesting adverse influences of excess gonadotropin use on IVF outcomes. Although an aggressive approach to controlled ovarian hyperstimulation results in a statistically significant reduction in cycle cancellations, the excessive use of gonadotropins detrimentally influences live birth after IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 25 publications
(36 reference statements)
4
56
0
3
Order By: Relevance
“…These observations agree with previous reports, that showed that a high Gn dose is effective in getting more oocytes [8,24] and avoiding cycle cancellation [8], but does not improve IVF results [6][7][8]24]. This could be due to a negative impact of high Gn dose on endometrial quality [25] or, alternatively, to the fact that a high dose of exogenous Gn could force the recruitment of "resistant" follicles, hosting oocytes of poor quality from which poor competence embryos derive [26].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These observations agree with previous reports, that showed that a high Gn dose is effective in getting more oocytes [8,24] and avoiding cycle cancellation [8], but does not improve IVF results [6][7][8]24]. This could be due to a negative impact of high Gn dose on endometrial quality [25] or, alternatively, to the fact that a high dose of exogenous Gn could force the recruitment of "resistant" follicles, hosting oocytes of poor quality from which poor competence embryos derive [26].…”
Section: Discussionsupporting
confidence: 91%
“…In the last years, the most frequently used COH regimen for expected poor responders has been the "long" protocol with a high daily Gn dose (300-450 IU/d) [4]. Unfortunately, however, despite the higher number of retrieved oocytes this regimen failed to improve the final IVF success rate, implying, on the other side, a relevant increase of economical costs of IVF procedure [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these deficiencies, besides reducing the impact of ovarian stimulation [41], one of the main goals of human assisted reproduction-related research is the improvement of culture conditions. This has led on one side to the use of chemically defined media containing growth factors [33], on the other side to the development of culture systems employing co-culturing with growth factor-releasing cells [47], so that dramatic improvements in the composition of embryo culture media have been made in the last 15 years allowing the efficient production of viable human blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it reduces the amount of FSH and days needed for proper stimulation, parameters directly linked to the chance of pregnancy [41].…”
Section: Introductionmentioning
confidence: 99%